Exploration of adjunct faculty engagement in student success initiatives within a community college system - Sramek, Jennifer (Kansas State University, 2023)
Community colleges rely heavily on their adjunct faculty to provide instruction; however, institutions often fail to fully engage and support adjunct faculty in the work of student success. Although adjunct faculty represent approximately two thirds of all faculty at community colleges (American Association of University Professors [AAUP], 2018), the American Federation of Teachers (AFT, 2020) indicated they work under challenging conditions with limited support from their institutions. The purpose of this multisite case study was to examine strategies to engage adjunct faculty members in student success initiatives in a community college system and understand the adjunct faculty members’ perceptions of these strategies. Understanding the adjunct faculty perspective is critical for institutions to make meaningful changes to policies and practices designed to enhance engagement of adjunct faculty. Findings from the research indicated the community college system designed policies and practices to engage adjunct faculty in student success initiatives. Policies and practices were created to address hiring practices, compensation/benefits, and working conditions. In addition, the community college system committed to invest in their employees through orientation, professional development, support and communication, performance evaluations, and recognition and reward of adjunct faculty contributions. The success of these strategies relied on consistency of implementation, communication, and fostering connections for adjunct faculty in the community college system.
Keywords: Adjunct faculty; Student success initiatives; Community college system